PENGEMBANGAN ASSESSMENT UNTUK MENGUKUR KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI BAHAYA MENGKONSUMSI MINUMAN KERAS, JUDI DAN PERTENGKARAN DI SMPN 06 BENGKULU SELATAN - Rahma Utami, Delsa; Mindani; Syarifin, Ahmad (JPT : Jurnal Pendidikan Tematik, 2021)
This study aims to develop an assessment to measure critical thinking skills on the dangers of consuming alcohol, gambling and fighting.The research method used is Research and Development (RnD) research which consists of 8 steps, which include:Potentials And Problems, Product Planning, Initial Product Development, Expert Validation, Expert Revision, Product Trial, Product Revision, and Final Product.The purpose of this development research is to develop an assessment to measure the critical thinking skills of students of SMPN Bengkulu Selatan on the subject of Dangers of Consuming Alcohol, Gambling and Quarrels in the subject of Islamic Religious Education.The assessment made consists of 20 items in the form of multiple choice that measure students' critical thinking skills which are compiled using critical thinking indicators such as interpretation (interpretation), analysis (analysis), inference (inference), and evaluation (evaluation).The trial subjects in this research and development are expert subjects, namely assessment experts, material experts and linguists, as well as the subject of class VIII students of SMPN 06 Bengkulu Selatan as product users.Data were analyzed descriptively qualitatively and quantitatively.The feasibility of the assessment by three validator experts, namely the assessment expert, material expert and linguist, which was developed on the assessment aspect by 83%, material aspect by 82%, and 95% language aspect, overall was declared very feasible with an average of 86%.This means that the assessment to measure critical thinking skills is stated to be very feasible to use in measuring the level of students' critical thinking skills.